LEGAL PROTECTION FOR THE WINNER OF AN AUCTION FOR THE EXECUTION OF COLLATERAL RIGHTS DUE TO OPPOSITION FROM THE PREVIOUS DEBTOR (STUDY OF DECISION NUMBER 31/PDT.G/2016/PN PLK) - Fauziah Zahrani; Fransisco; Evi; Novea Elysa Wardhani (International Journal of Cultural and Social Science, 2026)
This article evaluates the effectiveness of legal protection for auction winners in executing Mortgage Rights and the practical enforceability of the Mortgage Rights Certificate. While the Mortgage Law provides creditors with privileged authority for parate execution under Articles 6 and 14, execution is often hindered when the debtor or possessor files an objection (derden verzet). The research uses a normative legal method, examining the Mortgage Law, Indonesian Civil Procedure Code, Ministry of Finance Regulation 122/2023, and relevant court decisions. The findings suggest that legal protection for auction winners is inadequate due to insufficient preventive measures, such as execution seizure before the auction. This allows objections to delay execution for years. Additionally, Article 195 of the Civil Procedure Code lacks clear time or scope limitations for resistance, enabling its misuse. The research recommends mandatory execution seizure before auction and stricter court standards for accepting execution delay requests, enhancing parate execution effectiveness and auction winner protection.